Repeat procedures after pulsed field ablation for atrial fibrillation: MANIFEST-REDO study - Scherr, Daniel; Turagam, Mohit K; Maury, Philippe; Blaauw, Yuri; van der Voort, Pepijn; Neuzil, Petr; Reichlin, Tobias; Metzner, Andreas; Vijgen, Johan; Kautzner, Josef; Boveda, Serge; Anic, Ante; et al. (Europace, 2025)
AIMS: Initial clinical studies of pulsed field ablation (PFA) to treat atrial fibrillation (AF) indicated a >90% durability rate of pulmonary vein isolation (PVI). However, these studies were largely conducted in single centres and involved a limited number of operators. We aimed to describe the electrophysiological findings and outcomes in patients undergoing repeat ablation after an initial PF ablation for AF. METHODS AND RESULTS: In the MANIFEST-REDO study, we investigated patients who underwent repeat ablation due to clinical recurrence-AF or atrial tachycardia (AT)-following first-ever PVI with a pentaspline PFA catheter (Farawave, Boston Scientific Inc.). At 22 centres, 427 patients (age 64 ± 11 years; 37% female) were included. Of note, the recurrent arrhythmia leading to the repeat ablation was paroxysmal AF (51%), persistent AF (30%), or AT (19%). At the repeat procedure, the PV reconnection rates were 30% (left superior pulmonary vein), 28% (left inferior pulmonary vein), 33% (right superior pulmonary vein), and 32% (right inferior pulmonary vein). In 45% of patients, all PVs were durably isolated at the beginning of the repeat procedure, with the previous use of any imaging or mapping modality being univariately associated with durable PVI. After a post-redo follow-up period of 284 (90-366) days, the primary effectiveness endpoint (freedom from documented AF/AT lasting ≥30 s after 3-month blanking without class I/III antiarrhythmic drugs or symptoms) was achieved in 65% of patients, with significant differences between groups (PAF 65% vs. PersAF 56% vs. AT 76%; P = 0.04). Persistent AF as recurrent arrhythmia after the initial PFA ablation predicted AT/AF recurrence after repeat ablation [hazard ratio 1.241 (95% confidence interval 1.534-1.005); P = 0.045]. The procedural complication rate was 2.8%. CONCLUSION: In repeat procedures for AF/AT performed after an index procedure with PFA for AF, PV reconnections are not uncommon. Repeat procedures can be performed safely and with an acceptable subsequent success rate.
Keywords: výsledek terapie; Recurrence; Pulmonary vein isolation; Male; Risk Factors; Heart Rate; Aged; mužské pohlaví; senioři; srdeční frekvence; Catheter Ablation; recidiva; Atrial Fibrillation; Pulmonary Veins; Treatment Outcome; Time Factors; Electroporation; lidé; akční potenciály; Action Potentials; ženské pohlaví; supraventrikulární tachykardie; Atrial tachycardia; Pulsed field ablation; Humans; časové faktory; rizikové faktory; Electrophysiologic Techniques, Cardiac; venae pulmonales; elektrofyziologické techniky kardiologické; Atrial fibrillation; Reoperation; katetrizační ablace; Female; Tachycardia, Supraventricular; lidé středního věku; reoperace; fibrilace síní; Middle Aged